Pemodelan Simulasi Antrian Pengambilan Material Pada Warehouse Section PT Kaltim Methanol Industri - Putri Gesan Prabawa Anwar; Christopher Davito Prabandewa Hertadi; Ridho Kamal Pratama (Universitas Islam Raden Rahmat, Malang, 2024)
A company that offers products naturally needs storage space called a warehouse. Warehouse has an information system regarding the availability, status and condition of goods in the warehouse. Parties who need materials are required to come to the warehouse to pick up the goods. With limited human resources, there will be a buildup of queues and waiting times that are getting longer along with the number of users entering the system. This study aims to reduce the number and time of queues by conducting simulations with different scenarios. The study used primary data by combining 3 days of observation data as many as 34 data. Observations were made during normal working hours, namely 07.30 to 15.30. The actual model of the warehouse queuing system is a single channel multiphase. By comparing the actual simulation model with different scenarios, it is expected to find scenarios that can reduce the time and number of queues.